The Influence of Audit Findings, Follow-Up on Recommendations, and Adequacy of Financial Statement Disclosures on Audit Opinions of Regencies and Cities in Lampung Province - Mutiara Zuryatina; Anggeraini Oktarida; Riza Wahyudi (Jurnal Akuntansi dan Keuangan, 2025)
Examine the influence of audit findings, follow-up actions on audit recommendations, and the adequacy of financial statement disclosures on audit opinions of local government financial statements in Lampung Province from 2019–2023 are the aims of this research. A quantitative approach is adopted by this study, using secondary data from the official website, www.bpk.go.id. The entire population was sampled using a saturated sampling technique with a total of 75 samples in the form of LKPD from districts/cities in Lampung Province taken from 15 entities. This study used SPSS version 26 to conduct a logistic regression analysis. Based on the results of the study, it was found that audit findings partially had a significant negative influence on audit opinions. On the other hand, follow-up on recommendations on audit results and the adequacy of financial statement disclosure did not significantly influence audit opinions. The results of the simultaneous test indicated that the variables Audit Findings, Follow-Up on Recommendations, and Adequacy of Financial Statement Disclosure collectively significantly influenced the Local Government Financial Statements (LKPD) of districts/cities in Lampung Province.